Cabergoline, a long-acting dopamine agonist, attenuates L-dopa-induced dyskinesia without L-dopa sparing in a rat model of Parkinson's disease. (May 2022) - Nishijima, Haruo; Mori, Fumiaki; Kimura, Tamaki; Miki, Yasuo; Kinoshita, Iku; Nakamura, Takashi; Kon, Tomoya; Suzuki, Chieko; Wakabayashi, Koichi; Tomiyama, Masahiko
Abstract: Intermittent administration of L -dopa in Parkinson's disease is associated with L -dopa-induced dyskinesia (LID). Long-acting dopamine agonists may reduce the risk of LID by continuous dopaminergic stimulation. We examined the LID-like behavior, preprodynorphin messenger ribonucleic acid (mRNA) expression in the striatum (a neurochemical LID hallmark), and the volume of the entopeduncular nucleus (a pathological LID hallmark) in Parkinson's disease rat models that were treated with L -dopa and cabergoline. Cabergoline co-treatment with L -dopa reduced LID, striatal preprodynorphin mRNA expression, and hypertrophy of the entopeduncular nucleus, indicating that cabergoline has an anti-LID effect independent of the L -dopa-sparing effect. Highlights: Cabergoline is a long-acting dopamine agonist. Cabergoline co-treatment with L -dopa reduced L -dopa-induced dyskinesia in model rats. Cabergoline co-treatment decreased striatal preprodynorphin mRNA expression. Cabergoline co-treatment suppressed hypertrophy of the entopeduncular nucleus. Cabergoline has an anti-dyskinesia effect independent of the L -dopa-sparing effect.